Effect of endodontic chelating solutions on the bond strength of endodontic sealers - Behram TUNCEL; Emre NAGAS; Zafer CEHRELİ; Ozgur UYANIK; Pekka VALLITTU; Lippo LASSILA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The purpose of this in vitro study was to evaluate the effect of various chelating solutions on the radicular push-out bond strength of calcium silicate-based and resin-based root canal sealers. Root canals of freshly-extracted single-rooted teeth (n = 80) were instrumented by using rotary instruments. The specimens were randomly divided into 4 groups according to the chelating solutions being tested: (1) 17% ethylenediaminetetraacetic acid (EDTA); (2) 9% etidronic acid; (3) 1% peracetic acid (PAA); and (4) distilled water (control). In each group, the roots were further assigned into 2 subgroups according to the sealer used: (1) an epoxy resin-based sealer (AH Plus) and (2) a calcium silicate-based sealer (iRoot SP). Four 1 mm-thick sections were obtained from the coronal aspect of each root (n = 40 slices/group). Push-out bond strength test was performed at a crosshead speed of 1 mm/min., and the bond strength data were analyzed statistically with two-way analysis of variance (ANOVA) with Bonferroni's post hoc test (p < 0.05). Failure modes were assessed quantitatively under a stereomicroscope. Irrespective of the irrigation regimens, iRoot SP exhibited significantly higher push-out bond strength values than AH Plus (p < 0.05). For both the sealers, the use of chelating solutions increased the bond strength, but to levels that were not significantly greater than their respective controls (p > 0.05). iRoot SP showed higher resistance to dislocation than AH Plus. Final irrigation with 17% EDTA, 9% Etidronic acid, and 1% PAA did not improve the bond strength of AH Plus and iRoot SP to radicular dentin.